#TITLE_ALTERNATIVE# - CRYSTINA PARERA (NIM 12206090); Pembimbing: Prof. Dr. Ir. Septoratno Siregar D.E.A., GABRIELA
Polymer injection is one of Enhanced Oil Recovery (EOR) methods which can increase recovery factor. Polymer solution will decrease the water mobility so that the possibilities of water flow bypassing the oil flow will be smaller. CMC-AM is considered as an alternative for polymer injection because it is made from material which is widely available in Indonesia. Cellulose of the palm oil empty fruit bunch and acrylamide are used as the polymer raw material. The main purpose of the laboratory study is to investigate performance of biopolymer CMC-AM in improving recovery factor by comparing its rheology and recovery factor (RF) results with water flooding and a widely used polymer type, HPAM. Rheology observation shows that CMC-AM behaves as non-Newtonian fluid. Compared with concentration of HPAM solution, higher CMC-AM concentration is needed to reach certain viscosity value. Observation results show that CMC-AM has better resistance towards temperature and shear rate than HPAM. CMC-AM also has better resistance than HPAM at salinity below 20,000 ppm. Applicability of polymer flooding depends on channels within the reservoir, size of polymer molecules, and pore size of the rock. From core set 1 analysis, very low RF obtained from water injected core might be due to high water saturation which inhibits oil to flow. While very high RF obtained from CMC-AM injected core might be caused by channels within the core that couldn't be plugged by polymer molecules. From core set 3 analysis, highest RF obtained by water injected core might be caused by channels within the core.